TERAPI MUSIK UNTUK MENURUNKAN KECEMASAN: LITERATUR REVIEW - Sholikhah, Zumrotus; Bratha, Shinta Dewi Kasih (Ensiklopedia of Journal, 2025)
Abstract: Anxiety is a common psychological phenomenon experienced by many people and is a fairly common mental disorder worldwide. Some studies have shown that music therapy can reduce the anxiety of individuals. Nonetheless, there are many different theories and research findings on how it can help people lower anxiety. One of the non-pharmacological therapies to treat anxiety is music therapy. This literature review aims to determine the effect of music therapy on patient anxiety levels. Quantitative research with a literature review approach with a search method using a google scholar data base. Journal years used in the last 10 years. The results of the analysis of 20 journals illustrate that music therapy can reduce anxiety.Keywords: Therapy, Music, Decline, Anxiety